2016
DOI: 10.1111/hepr.12694
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sleep disorders in chronic hepatitis C patients treated with interferon‐based therapy and direct acting antivirals using actigraphy

Abstract: Interferon-based triple therapy in patients with CHC may cause significant sleep disturbances. Interferon-free DAA therapy is less likely to deteriorate sleep conditions in patients with CHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…It is clear from our study that daytime somnolence and sleep disturbances in patients with HCV infection were ameliorated by DAA treatment. A previous report revealed that the PSQI score improved during DAA treatment . Restless leg syndrome also causes sleep disturbances.…”
Section: Discussionmentioning
confidence: 93%
“…It is clear from our study that daytime somnolence and sleep disturbances in patients with HCV infection were ameliorated by DAA treatment. A previous report revealed that the PSQI score improved during DAA treatment . Restless leg syndrome also causes sleep disturbances.…”
Section: Discussionmentioning
confidence: 93%
“…With regards to the physical activity data, only few studies have availed of actigraphy for capturing activity patterns in HCV‐infected patients . To date, Heeren et al assessed motion drive and intensity of physical activity by actigraphy and detected no differences when comparing patients with hepatitis C to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the physical activity data, only few studies have availed of actigraphy for capturing activity patterns in HCV-infected patients. 24,35 To date, Heeren et al 24 assessed motion drive and intensity of physical activity by actigraphy and detected no differences when comparing patients with hepatitis C to healthy controls. One might have expected increases in physical activity to accompany the reduced fatigue in our patients; however, this reduction could have affected other aspects of their lives, since fatigue can manifest in different ways.…”
Section: F I G U R E 3 Severity Of Depression According To Total Bdi-iimentioning
confidence: 99%
“…It is the size of a wristwatch, and can be worn without interfering with the normal activity of daily life. [33][34][35][36] DATA COLLECTION A research assistant will collect data elements from patient medical records, including the following at baseline (figure 1):…”
Section: Case Registration Periodmentioning
confidence: 99%